Comparative Studies on Educational Governance: Balancing Centralization and Decentralization in Global Contexts - Hamad bin As-Siddiqi; Aisya El- Bukhary (PT Mutiara Bustan Ilmu, 2025)
This study explores the dynamics of educational governance by comparing centralized and decentralized systems across global contexts. The research examines how centralization contributes to equity, accountability, and national standards, while decentralization promotes flexibility, community engagement, and contextual responsiveness. Through a comparative analysis of diverse educational systems, the study highlights the strengths and limitations of each governance model and reveals the growing relevance of hybrid approaches that integrate both paradigms. Findings suggest that educational reforms must adapt to cultural, political, and socio-economic realities rather than adopt a one-size-fits-all strategy. The paper emphasizes that sustainable educational governance requires balancing national coherence with local autonomy to ensure both equity and innovation. This research contributes to the field of comparative and international education by offering insights into how global governance trends can inform effective policy-making that is responsive to contemporary challenges.